Acibenzolar‐S‐methyl activates phenylpropanoid pathway to enhance resistance against Alternaria alternata in pear fruit. (13th September 2022) - Guo, Yan; Li, Xue; Li, Canying; Jinyue, Ruxin; Xu, Hengping; Ge, Yonghong
Abstract: BACKGROUND: Alternaria alternata is a causal agent of black spot rot of pear fruit after harvest. Acibenzolar‐ S ‐methyl (ASM) has been shown to be a potential elicitor of tolerance in several horticultural products. This work was performed to research the influence of ASM on black spot rot of Docteur Jules Guyot pears and vital enzyme activity and gene expression in the phenylpropanoid pathway. RESULTS: ASM remarkably decreased the lesion diameter of A. alternata ‐inoculated pears. ASM also increased phenylalanine ammonialyase, cinnamate 4‐hydroxylase, cinnamyl alcohol dehydrogenase, peroxidase, polyphenol oxidase activities and gene expression, and enhanced 4‐coumarate/coenzyme A ligase activity in pears. Moreover, ASM improved the content of phenylalanine, total phenolic compounds, caffeic acid, flavonoids, anthocyanin and lignin in pears. CONCLUSION: ASM could modulate vital enzyme activity and gene expression in the phenylpropanoid pathway to accelerate metabolite synthesis, thereby enhancing resistance against A. alternata in pears. © 2022 Society of Chemical Industry.